Sodium thiosulfate attenuates angiotensin II-induced hypertension, proteinuria and renal damage - Snijder, Pauline M; Frenay, Anne-Roos S; Koning, Anne M; Bachtler, Matthias; Pasch, Andreas; Kwakernaak, Arjan J; van den Berg, Else; Bos, Eelke M; Hillebrands, Jan-Luuk; Navis, Gerjan; Leuvenink, Henri G D; van Goor, Harry (Nitric oxide, 2014)
Hypertension and proteinuria are important mediators of renal damage. Despite therapeutic interventions, the number of patients with end stage renal disease steadily increases. Hydrogen sulfide (H(2)S) is an endogenously produced gasotransmitter with vasodilatory, anti-inflammatory and antioxidant properties. These beneficial characteristics make H(2)S an attractive candidate for pharmacological use in hypertensive renal disease. We investigated the protective properties of H(2)S in angiotensin II (Ang II)-induced hypertensive renal disease in rats. Treatment with the H(2)S donor NaHS and major H(2)S metabolite sodium thiosulfate (STS) during three weeks of Ang II infusion reduced hypertension, proteinuria, oxidative stress and renal functional and structural deterioration. In an ex vivo isolated perfused kidney setup, NaHS, but not STS, reduced intrarenal pressure. The effect of NaHS could partially be explained by its activation of the ATP-sensitive potassium channels. In conclusion, treatment with H(2)S attenuates Ang II-associated functional and structural renal deterioration, suggesting that intervention in H(2)S production pathways has potential therapeutic benefit and might be a valuable addition to the already existing antihypertensive and renoprotective therapies.